Pengaruh Good Corporate Governance, Firm Age, Firm Size, Debt Rasio Terhadap Nilai Perusahaan Dengan Manajemen Risiko Perusahaan Sebagai Variabel Intervening - Shindyota Kristi Duana; Edi Subiyantoro; Nanik Sisharini (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the influence of Good Corporate Governance (GCG), Firm Age, Firm Size, and Debt Ratio on firm value, with risk management as an intervening variable. The research population includes 95 companies in the food and beverage manufacturing sector listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. The analysis method used is path analysis with the Sobel test to examine mediation effects. The results indicate that GCG, Firm Age, and Firm Size have a significant positive effect on firm value, with coefficients of 1.720 (p=0.015), 0.060 (p=0.004), and 0.120 (p=0.003), respectively. Debt Ratio has a positive effect on firm value (B=0.025, p=0.007), contrary to the initial hypothesis. Risk management mediates the positive relationship between GCG (Sobel test=1.183, p=0.030), Firm Age (Sobel test=1.426, p=0.050), and Debt Ratio (Sobel test=1.178, p=0.000) on firm value, but does not mediate the relationship between Firm Size and firm value (Sobel test=0.325, p=0.683). The coefficient of determination (R²) of 7.9% indicates that the independent and intervening variables explain 7.9% of the variation in firm value.